Influência da porcentagem de ferro na resistência a corrosão de revestimento depositado por soldagem de liga de inconel 625 sobre aço carbono - Cunha, Alexandre Borghi (2020)
This work aims to evaluate the corrosion resistance of specimens with metallic welding overlay in the MIG process with Inconel 625 alloy (ERNiCrMo-3) with iron percentages in the last layer of the overlay varying among 5%, 8%, 15% and 20%. Corrosion tests were carried out according to ASTM G-48, method A, having as acceptance criterion the NORSOK M-601 standard with test temperature of 50°C and time of 24 hours, as applied in manufacturing techniques, each sample of tests with different percentages of iron, in order to check which iron limit will not affect the corrosion resistance properties of the alloy. The percentage of iron was evaluated by means of chemical analysis in the specimens before the corrosion test. The metallographic analysis indicated a dendritic structure with relatively small secondary branch spacing, due to the high cooling rate in the solidification process imposed by the welding deposition process. The interdendritic regions indicated the precipitation of phases that, according to the bibliographic review, can collaborate with the corrosion process. After the corrosion test, an analysis of the topography resulting from the chemical attack was carried out in order to verify the presence of pitting, and to characterize this region by Scanning Electron Microscopy (SEM). The presence of secondary phases was observed in the boundary of the dendrites in this alloy of Inconel 625. Corrosion due to pitting formation only began to be noticed for the highest iron content (20%), indicating that the requirements in terms of standards for these overlay it is quite conservative in these test conditions.